2002
DOI: 10.1007/s10038-002-8654-5
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of autosomal dominant polycystic kidney disease in Japanese

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is one of the most common hereditary disorders. The prevalence of the ADPKD genotype in the Caucasian and Latin populations has been reported. Here, we used linkage analysis to demonstrate the prevalence of the genotype and the correlation between phenotypes and genotypes among 21 Japanese ADPKD families consisting of 96 individuals and including 57 affected members. Six polymorphic markers, each linked to either the polycystic kidney disease 1 (PKD1) or pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…The percentage of non-autosomal dominant PKD patients is also less than 10% among different populations (3,4). Several studies from around the world report similar results as mentioned above; for example Mizoguchi et al in 21 Japanese ADPKD families, including 96 individuals and 57 affected members, reported that 17 families (81%) had linkage to PKD1, 2 families (10%); PKD2 and 2 families did not have linkage to either PKD1 or PKD2 (14). Another study was performed by colleagues on 48 Korean families that the results were composed of PKD1 (79%) and PKD2 (21%) (15).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The percentage of non-autosomal dominant PKD patients is also less than 10% among different populations (3,4). Several studies from around the world report similar results as mentioned above; for example Mizoguchi et al in 21 Japanese ADPKD families, including 96 individuals and 57 affected members, reported that 17 families (81%) had linkage to PKD1, 2 families (10%); PKD2 and 2 families did not have linkage to either PKD1 or PKD2 (14). Another study was performed by colleagues on 48 Korean families that the results were composed of PKD1 (79%) and PKD2 (21%) (15).…”
Section: Discussionsupporting
confidence: 65%
“…The calculation of LOD scores for this two-point linkage analysis was done via the FASTLINK software. The resultant data in each family were integrated by means of Bayesian weighting formula for the likelihood estimation of a family to one or other locus (14). The genotyping of individuals includes descendent and married-in patients, where extracted and the founders of genotypes were reconstructed.…”
Section: Linkage Analysis and Haplotype Constructionmentioning
confidence: 99%
“…Furthermore, these two markers are known as suitable markers for ADPKD genetic testing in most studied populations. [ 8 13 14 15 ] In addition, for the first time, we found D16S475 to be highly informative in our population. This marker has also been reported as a suitable marker in some other studies.…”
Section: Discussionsupporting
confidence: 58%
“…Among the microsatellite markers reported in the PKD1 gene region, two extragenic markers, i.e., D16S475 and D16S291, and one intragenic marker, i.e., D16S3252 have been shown to have a high degree of heterozygosity (HET). [ 13 14 15 16 ] However, investigation of these markers has been rarely performed in the Iranian population. In this study, the HET and polymorphism information content (PIC) values for the PKD1 markers D16S475, D16S291, and D16S3252 were determined in a normal population of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…There is an argument about the existence of PKD3, however, no more genes have been identified. 6,7 The severity of renal disease in ADPKD is highly variable ranging from neonatal death, through typical presentations with end-stage renal disease (ESRD) in the sixth decade to adequate function into old age. 8 The phenotypic variability is due to heterogeneity at the genic and allelic levels as accepted.…”
Section: Introductionmentioning
confidence: 99%